2011
DOI: 10.1093/hmg/ddr600
|View full text |Cite
|
Sign up to set email alerts
|

A single administration of morpholino antisense oligomer rescues spinal muscular atrophy in mouse

Abstract: Spinal muscular atrophy (SMA) is an autosomal-recessive disorder characterized by α-motor neuron loss in the spinal cord anterior horn. SMA results from deletion or mutation of the Survival Motor Neuron 1 gene (SMN1) and retention of SMN2. A single nucleotide difference between SMN1 and SMN2 results in exclusion of exon 7 from the majority of SMN2 transcripts, leading to decreased SMN protein levels and development of SMA. A series of splice enhancers and silencers regulate incorporation of SMN2 exon 7; these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
240
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 235 publications
(253 citation statements)
references
References 75 publications
10
240
1
2
Order By: Relevance
“…Consistent with this interpretation, using a conditional knockout strategy, Park et al (2010) recently found that 70% of mice with selective depletion of SMN in motor neurons survived over a year. Porensky et al (2012) reported that ICV injection of PMO ASO10-29 at a dose of 27, 54, or 81 mg in the SMND7 model (which has a slightly milder phenotype than the severe model that we used here) led to a sixfold to sevenfold survival increase; the investigators proposed that early and sustained increase of SMN in the CNS is essential for SMA therapy. However, the strong survival increase that they reported was less striking than what we obtained in the more severe model with peripheral rescue alone.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Consistent with this interpretation, using a conditional knockout strategy, Park et al (2010) recently found that 70% of mice with selective depletion of SMN in motor neurons survived over a year. Porensky et al (2012) reported that ICV injection of PMO ASO10-29 at a dose of 27, 54, or 81 mg in the SMND7 model (which has a slightly milder phenotype than the severe model that we used here) led to a sixfold to sevenfold survival increase; the investigators proposed that early and sustained increase of SMN in the CNS is essential for SMA therapy. However, the strong survival increase that they reported was less striking than what we obtained in the more severe model with peripheral rescue alone.…”
Section: Discussionmentioning
confidence: 79%
“…In addition, as stated above, some of the ASO injected into the CNS is cleared with CSF into the blood and circulates to peripheral tissues. Porensky et al (2012) reported no statistically significant peripheral effect on SMN2 splicing after ICV injection of the middle dose; however, this may be attributable to the small sample size (n = 2), as an approximately twofold increase in SMN2 full-length mRNA in the liver and heart was actually observed. A more recent study using 25mer PMO (PMO25) confirmed that systemic delivery at high doses robustly rescues severe SMA mice (Zhou et al 2013).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…18,[53][54][55][56] We aimed to test a situation suitable for future patient care and chose oral application beginning on the first day of life (P0). Protein analysis of SMA animals at different disease stages demonstrates that there may be organ as well as time-dependent effects of HDACi treatment on SMN levels.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting the intron splice silencer N1 (ISS-N1) site within intron 7, by deletion or SSOmediated splice switching, improves exon 7 inclusion (9, 10). ISS-N1-targeted SSOs used to treat presymptomatic severely affected neonatal SMA mice, via systemic or intracerebroventricular administration, extend survival from 10 to >100 d (11,12). Although SSO targeting to the CNS is essential, there is also evidence for a peripheral role for the SMN in SMA (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
mentioning
confidence: 99%